2018
DOI: 10.1002/col.22338
|View full text |Cite
|
Sign up to set email alerts
|

Product color emotional design considering color layout

Abstract: Emotional experience and demand for product colors are important factors in users' decisions to buy and use a product. Therefore, accurately characterizing users' emotional responses of the product's color has become a significant consideration for product color design. However, a product color design problem exists in which it is challenging to accurately and efficiently position users' color image space because consumers have completely different image perceptions when encountering a large number of color sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
(15 reference statements)
0
15
0
Order By: Relevance
“…Such evolution suggests that designers must differentiate products to meet the emotional needs and preferences of different users. 43 According to the above studies, it can be further argued that product colour image refers to a perceptual and psychological response to seeing the colour of a product. Moreover, if only for a colour image, it refers to the perception generated when seeing the colour.…”
Section: Colour Image and Symbolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Such evolution suggests that designers must differentiate products to meet the emotional needs and preferences of different users. 43 According to the above studies, it can be further argued that product colour image refers to a perceptual and psychological response to seeing the colour of a product. Moreover, if only for a colour image, it refers to the perception generated when seeing the colour.…”
Section: Colour Image and Symbolismmentioning
confidence: 99%
“…70 Perceptual engineering also advocates the use of this method to find colour-emotional associations of products. 43 Studies on colour meaning and association are extended from the three main factors concluded by Osgood et al 54,69,71 ; that is, evaluation, potency and activity. Descriptions such as active/passive, warm/cool or heavy/light, explore the relationship between colour and a product or environment.…”
Section: Colour-emotion Associationmentioning
confidence: 99%
“…Lively and bright colors can strongly arouse their interest. [5] Generally, bright, refreshing and vivid colors are their favorite. They have their preference to colors.…”
Section: The Color Design Of Auxiliary Equipment Of Ct Machinementioning
confidence: 99%
“…A reasonable product color scheme can capture consumers' visual attention, enhance their psychological identity and sense of pleasure to the product, which further influence consumers' brand judgment and purchase decisions on products 2 , 3 . To this end, many scholars have carried out research in different aspects, including image color reuse 4 , product color planning 5 , product color evaluation 6 , product color emotion 7 , product color imagery 8 , product color aesthetics 9 , and color trend prediction 10 . Among them, the image color reuse is to extract the flat image color style in the process of product design, where the flat images is an important source of inspiration for designers to carry out product color scheme design 4 .…”
Section: Introductionmentioning
confidence: 99%